The metaverse dilemma : challenges and opportunities for business and society - Krishnan, Chitra,; Behl, Abhishek,; Dash, Snigdha,; Yadav, Prashant Dev, (Emerald Publishing Limited, 2024)
As with any digital technology, there are concerns about how new advancements may affect our health, safety, security, privacy, and economy. The metaverse has potential, but as with any other universe, whether it be physical or digital, it also faces challenges. It is currently undefinable; neither good nor bad can be applied to it, falling under a spectrum that can be either advantageous or harmful to those who engage in it. Focusing on the main issues presented by the metaverse, including implementation, governance, ethical decision-making, sustainability, safety and security, intellectual property, and acceptable behavior issues, The Metaverse Dilemma explores a balanced viewpoint of the metaverse from both a theoretical and practical mindset, examining the challenges and opportunities faced when adopting and implementing the metaverse in business and everyday scenarios. Contributing to the fields of technology and sustainability through the lens of the metaverse, The Metaverse Dilemma is essential reading for entrepreneurs, start-up enthusiasts, students, researchers, and practitioners looking to understand the broader implications of the metaverse on the future of global society.